2012
DOI: 10.1631/jzus.b1100120
|View full text |Cite
|
Sign up to set email alerts
|

New developments in small molecular compounds for anti-hepatitis C virus (HCV) therapy

Abstract: Abstract:Infection with hepatitis C virus (HCV) affects approximately 170 million people worldwide. However, no vaccine or immunoglobulin is currently available for the prevention of HCV infection. The standard of care (SOC) involving pegylated interferon-α (PEG-IFN α) plus ribavirin (RBV) for 48 weeks results in a sustained virologic response in less than 50% of patients with chronic hepatitis C genotype 1, the most prevalent type of HCV in North America and Europe. Recently, reliable in vitro culture systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 129 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Although it appears that biologics are favored over small molecule drugs, there are also several studies indicating that small molecule drugs were more successful than biologics, implying that the drug chemistry that carries the least risk is dependent on the disease [ 5 , 6 ]. For hepatitis C specifically, the tests and assays used in the development of the new drugs more accurately assess small molecule drugs and their targets; therefore these drugs are favored over biologics [ 23 ]. Small molecule drugs may be superior to biologics for hepatitis C simply based on what has previously been approved, but there are other factors, such as the drug targets as well as the available testing systems, that may have a larger impact on the outcome of the drug and that must be analyzed in conjunction with the drug chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears that biologics are favored over small molecule drugs, there are also several studies indicating that small molecule drugs were more successful than biologics, implying that the drug chemistry that carries the least risk is dependent on the disease [ 5 , 6 ]. For hepatitis C specifically, the tests and assays used in the development of the new drugs more accurately assess small molecule drugs and their targets; therefore these drugs are favored over biologics [ 23 ]. Small molecule drugs may be superior to biologics for hepatitis C simply based on what has previously been approved, but there are other factors, such as the drug targets as well as the available testing systems, that may have a larger impact on the outcome of the drug and that must be analyzed in conjunction with the drug chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that there are 120-180 million hepatitis C virus (HCV) carriers around the world, with the worldwide prevalence estimated at 3% (Shepard et al, 2005;Tong et al, 2012). Chronic hepatitis C is considered to be a major cause of liver disease, including progressive liver fibrosis, cirrhosis, and hepatocellular carcinoma (Hoofnagle, 2002;Shepard et al, 2005;Thomas and Seeff, 2005;Micallef et al, 2006;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Grazoprevir is a directly acting antiviral drug that inhibits the protease of the HCV [25]. Telaprevir, Boceprevir and Grazoprevir are approved inhibitors of PLPro of HCV [26][27][28][29]. Other notable compounds that were found to inhibit the SARS-CoV-2 PLPro include GRL0617, Mycophenolic acid and GRL0667 (Table 1).…”
Section: Discussionmentioning
confidence: 99%